Extracellular loops and ligand binding to a subfamily of Family A G-protein-coupled receptors. (20th July 2007) - Wheatley, M.; Simms, J.; Hawtin, S.R.; Wesley, V.J.; Wootten, D.; Conner, M.; Lawson, Z.; Conner, A.C.; Baker, A.; Cashmore, Y.; Kendrick, R.; Parslow, R.A.
Abstract : GPCRs (G-protein-coupled receptors) are a large family of structurally related proteins which mediate their effects by coupling to G-proteins. The V1a R (V1a vasopressin receptor) is a member of a family of related GPCRs that are activated by vasopressin {AVP ([Arg 8 ]vasopressin)}, OT (oxytocin) and related peptides. These receptors are members of a subfamily of Family A GPCRs called the neurohypophysial peptide hormone receptor family. GPCRs exhibit a conserved tertiary structure comprising a bundle of seven TM (transmembrane) helices linked by alternating ECLs (extracellular loops) and ICLs (intracellular loops). The cluster of TM helices is functionally important for ligand binding, and, furthermore, activation of GPCRs involves movement of these TM helices. Consequently, it might be assumed that the extracellular face of GPCRs is composed of peptide linkers that merely connect important TM helices. However, using a systematic mutagenesis approach and focusing on the N-terminus and the second ECL of the V1a R, we have established that these extracellular domains fulfil a range of important roles with respect to GPCR signalling, including agonist binding, ligand selectivity and receptor activation.